Doctor Honoris Causa otorgado por la Universidad Ricardo Palma al Dr. Alfredo Quiñones Hinojosa - De La Cruz Vargas, Jhony Alberto (2019)
The Doctor Honoris Causa, is the highest honorary title granted by the Ricardo Palma University, to eminent persons. They are conferred with zeal by our house of studies to very outstanding personalities of the national and international scope, who with their work and personal trajectory honor to the culture, the science and the humanity.I want to thank the Rector of the University for receiving the order, to make a brief sketch of Dr. Alfredo Quiñones Hinojosa. DOI:10.25176/RFMH.v19.n2.2003